Formulation and Evaluation of Moringa Seed Oil Nanoemulsion Gel - Tirmiara, Nita; Reveny, Julia; Silalahi, Jansen (Asian Journal of Pharmaceutical Research and Development, 2019)
Objective: The objective of this study was to formulate and evaluate the moringa seed oil (MSO) nanoemulsion gel using high-energy emulsification method. Methods: Nanoemulsion gel formulated by high-energy emulsification method using the comparison of surfactant (tween 80) and cosurfactant (sorbitol) concentration with the variation of moringa seed oil concentration. Evaluation of the stability of the nanoemulsion gel preparation includes centrifugation test, viscosity, pH, organoleptic observation (odor, color, clarity, and phase separation), and particle size measurement during 12 weeks storage at room temperature. Results: The results showed that all nanoemulsion gel preparations are transparent yellow, characteristic odor, type weights 1.0888–1.1193 g/ml, and stable for 12 weeks storage at room temperature. The smallest particle size produced by the nanoemulsion gel preparation in a formula of the concentration of 5%, which 52.25 nm. Conclusions: Moringa seed oil can be formulated as a nanoemulsion gel by high energy emulsification method. MSO with a 5% concentration was very stable for 12 weeks storage.